Diagnostic validity of peptic ulcer perforation scoring system in predicting mortality in patients with perforated peptic ulcer at a tertiary care hospital in India - Varun Kumar D,; Madhu BS,; Madhura Madhura, (Asian Journal of Medical Sciences, 2023)
Background: One of the prevalent ailments impacting the population of India is peptic ulcer. Although generally benign in its course, it can cause dangerous complications such as perforation and bleeding. Perforation is a life-threatening complication of the peptic ulcer. The status of patients may suddenly deteriorate if they wait too long to seek hospital care or if a diagnosis is delayed due to an unusual presentation. For triage and risk classification, it is critical to accurately and promptly identify high-risk surgical perforated peptic ulcer patients. Aims and Objectives: Perforations in peptic ulcer disease are known to cause considerable morbidity and mortality. The objective of this study was to verify the reliability of the peptic ulcer perforation (PULP) score in predicting patient death after surgery for PULP. Materials and Methods: This was a retrospective cross-sectional study included 50 PULP patients who underwent surgery and analyzed the data until discharge or death at tertiary care university hospital in India. Results: The mortality rate observed was 24%. Elderly population, raised serum creatinine, liver cirrhosis, steroid abuse, pre-operative shock, and American Society of Anesthesiologists (ASAs) grade were identified as risk factors for poor post-operative prognosis. The area under curve for mortality prediction was 0.947 for PULP score. Conclusion: Poor outcome was significantly higher in the elderly, patients with raised serum creatinine, pre-operative shock, and ASA. PULP score proved to be a more precise indicator of mortality. A larger study inclusive of other mortality risk prediction models would help formulate a more accurate and population specific scoring system.